The continuum of chronic tonsillitis from a general pathological standpoint - V. A. Belov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The continuum of transitional states is considered as a concept of the development of changes in the palatine tonsils from normal variants, through functional deviations and borderline states, to impaired function (from the development of chronic tonsillitis to the occurrence of various associated diseases). This process is based on changes occurring at different levels – from molecular genetic, biochemical and further into the field of clinical manifestations. In the development of chronic tonsillitis, starting from the first manifestations of the disease, the following stages can be distinguished: conditionally healthy, latent forms of the disease, active forms of the pathological process. The control of risk factors creates the basis for the transition from the treatment of chronic tonsillitis that has already arisen to preventive measures at the prenosological stage, a balanced and scientifically based personalized approach in the interests of the patient. Modeling of transient processes of the body state is possible on the way of building mathematical models.